The State Politics Against to Lesbian, Gay, Bisexual and Transgender (LGBT) in Medan City - Yeni Hartini (Program Doktor Akidah dan Filsafat Islam, 2019)
This thesis research aims to find out what causes LGBT, how they behave, and to find out how the state’s politics towards LGBT existence, especially in Medan City. The study results explain that the causes of LGBT in Medan City are influenced by two factors, namely internal and external. Internal factors arise because of the individual's encouragement and willingness to shape one’s character and external factors that come from outside the individual, which can encourage someone to have free sex caused by aspects of family and relationships.